DETERMINATION OF Cd, Pb, AND Zn IN FISH, WATER AND MUD FROM GHAZI GHAT OF INDUS RIVER (PUNJAB, PAKISTAN): A RELATIONSHIP BETWEEN QUANTITY OF METAL AND WEIGHT OF FISH - Yasin, Ghulam; Khokhar, Muhammad Younas (Journal of Research (Science), 2008)
Water, mud and fish samples were collected from the Ghazi Ghat of the river Indus (Punjab, Pakistan). Fish were dissected and their livers and muscles were analyzed. Wet digestion method was used for the digestion of fish and mud samples. All samples were analyzed for Cd2+, Pb2+ and Zn2+ by Flame Atomic Absorption Spectrometry (FAAS). Cadmium and Zinc were determined directly, while lead was pre-concentrated on cation-exchange resin microcolumn by Flow Injection Analysis (FIA) technique before analysis by FAAS. A relationship was found among water, mud and fish samples